2020
DOI: 10.1007/s00775-020-01788-x
|View full text |Cite
|
Sign up to set email alerts
|

Stable Hg(II)-mediated base pairs with a phenanthroline-derived nucleobase surrogate in antiparallel-stranded DNA

Abstract: Metal-mediated base pairs involving artificial nucleobases have emerged as a promising means for the site-specific functionalization of nucleic acids with metal ions. In this context, a GNA-appended (GNA: glycol nucleic acid) nucleoside analogue containing the artificial nucleobase 1H-imidazo[4,5-f][1,10]phenanthroline (P) has already been applied successfully in a variety of homo-and heteroleptic metal-mediated base pairs, mainly involving Ag(I) ions. Herein, we report a thorough investigation of the Hg(II)-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…5′-d(AAAAAAAAAPTAATTTTPAATATTT)-3′/ 3′-d(TTTTTTTTTCATTAAAATTTATAAA)-5′ it was possible to selectively load one modified base pair (P:T ) with Hg +2 and the other (P:C) with Ag + . A similar phenomenon was observed for a duplex 5′-d(GAGGGAPAGAAAG)-3′/3′-d(CTCCCTPTCTTTC)-5′ (a P:P base pair), where ΔTm = 4.3 °C was observed after addition of the Hg 2+ cation, although ΔTm = 14.5 °C was observed for a P:T base pair [54].…”
Section: Glycol and Butyl Nucleic Acids (Gna And Buna)supporting
confidence: 74%
“…5′-d(AAAAAAAAAPTAATTTTPAATATTT)-3′/ 3′-d(TTTTTTTTTCATTAAAATTTATAAA)-5′ it was possible to selectively load one modified base pair (P:T ) with Hg +2 and the other (P:C) with Ag + . A similar phenomenon was observed for a duplex 5′-d(GAGGGAPAGAAAG)-3′/3′-d(CTCCCTPTCTTTC)-5′ (a P:P base pair), where ΔTm = 4.3 °C was observed after addition of the Hg 2+ cation, although ΔTm = 14.5 °C was observed for a P:T base pair [54].…”
Section: Glycol and Butyl Nucleic Acids (Gna And Buna)supporting
confidence: 74%
“…[12] Later, the preference for a single isomer inside the DNA duplex was confirmed for other metal-mediated homo base pairs of P, involving the metal ions Cu I , Zn II , and Hg II . [14] In all cases, CD spectra clearly indicated that the metal-mediated base pair was indeed the isomer shown on the right-hand side of Figure 1b. Interestingly, this preference was observed irrespective of whether (R)-P or (S)-P were introduced as nucleoside analogues into the DNA duplex, despite their different behaviour outside of DNA.…”
Section: Introductionmentioning
confidence: 77%
“…[72][73][74][75] Such base pairs typically feature a dicoordinate bridging Hg II and a linear coordination geometry although with artificial nucleobase surrogates higher coordination numbers have been reported as well. [76] Various applications for coordinative Hg II -mediated base pairing are under active development, [63] ranging from sensors for Hg II [77][78][79][80][81] to molecular wires. [82] High affinity, rapid association and dissociation [83] and responsiveness of nucleic acid secondary structure to subtle changes in the binding mode [84] make Hg IImediated base pairs attractive components for the construction of DNA nanostructures.…”
Section: Hg II -Mediated Base Pairing Of Organomercury Nucleobasesmentioning
confidence: 99%
“…Most of the research efforts have been directed at coordinative Hg II ‐mediated base pairs, in particular the T‐Hg II ‐T homo base pair [72–75] . Such base pairs typically feature a dicoordinate bridging Hg II and a linear coordination geometry although with artificial nucleobase surrogates higher coordination numbers have been reported as well [76] . Various applications for coordinative Hg II ‐mediated base pairing are under active development, [63] ranging from sensors for Hg II[77–81] to molecular wires [82] .…”
Section: Hgii‐mediated Base Pairing Of Organomercury Nucleobasesmentioning
confidence: 99%